2016
DOI: 10.1144/sp432.9
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater recharge as the trigger of naturally occurring intraplate earthquakes

Abstract: I explore the hypothesis that most intraplate earthquakes and their aftershock sequences are triggered by pore-fluid pressure increases. As proposed in this paper, data from the magnitude 5.7 Virginia earthquake of 23 August 2011 show that this is a two-step process. (1) First, from areas where there is greater than normal meteoric recharge, pore-fluid pressure diffusion by means of Biot slow waves transfers more pore-fluid pressure towards a future hypocentre. Here the cumulation of Biot slow waves produces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…They argue that the most important factors are elastic thickness and heat flow, but also that Neoproterozoic fold belts show significantly higher seismicity, possibly owing to inherited zones of weakness. Costain (2016) discusses intraplate earthquakes and their aftershocks, triggered by groundwater recharge, with an example from North America. He provides a two-step model for the physical processes that influence crustal stress changes and might affect aftershock distributions.…”
Section: Topics/approachesmentioning
confidence: 99%
“…They argue that the most important factors are elastic thickness and heat flow, but also that Neoproterozoic fold belts show significantly higher seismicity, possibly owing to inherited zones of weakness. Costain (2016) discusses intraplate earthquakes and their aftershocks, triggered by groundwater recharge, with an example from North America. He provides a two-step model for the physical processes that influence crustal stress changes and might affect aftershock distributions.…”
Section: Topics/approachesmentioning
confidence: 99%
“…In the last decades, a number of studies have pointed out how surface/subsurface crustal (un)loading can influence stress perturbations thereby promoting fault slip in different tectonic contexts. Valuable examples come from reservoir impoundment (e.g., Gupta, ; Hua et al, ; Kebeasy & Gharib, ; Tuan et al, ), groundwater extraction (e.g., Amos et al, ; Gonzalez et al, ), sediment unloading by river erosion (Calais et al, ), continental water storage (e.g., Bettinelli et al, ; Chanard et al, ; Constain, ; Fu & Freymueller, ), tidal loading (Luttrell & Sandwell, ), ice and snow load (e.g., Heki, ; Hetzel & Hampel, ), and heavy precipitation (Hainzl et al, ). Roughly speaking, the removal of overburden can create stress perturbations that may have the potential to trigger earthquakes with reverse kinematics as observed for instance in NW Transverse Ranges (Yerkes et al, ) and northward of Lorca city (Gonzalez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…3With increased crustal permeability in the newly fractured zone pore-fluid pressure transients created by the main shock trigger aftershocks. Costain (2016) suggested that only 0.01 to 0.1 MPa (about 1 to 10 m of hydraulic head) of porefluid overpressure is generally sufficient to trigger an intraplate earthquake in the SOC crust but persistence of pore-fluid overpressure is a key factor in triggering intraplate seismicity. And he also suggested that depending on the hydraulic diffusivity of the crust there were one-to six-month time lags between groundwater recharge and the onset of seismicity.…”
Section: Methodsmentioning
confidence: 99%
“…However, our main theme of the research has been the relation between seismicity and hydrological cycle. Costain and Bollinger (2010) proposed that naturally occurring earthquakes anywhere on Earth belong to one of two types: (1) interplate seismicity associated with the dynamics of plate tectonics; and (2) intraplate seismicity associated with the dynamics of the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation